A Study of The Aspects of Turkey’s Organizational Behavior - Abdulkerim Yavuzaslan; Ahmet BARIŞÇIL; Charles G. Kamau (Qubahan Academic Journal)
In order to better understand the actions and reactions of those employed at a certain workplace or on the market, economists tend to use the knowledge accumulated by other social sciences, such as psychology, to study the behavior of these individuals when in a group. Though it already existed earlier, this field of interest, organizational behavior, has been at the forefront of the interest of Turkish researchers since the 1950s, the time of democratization and Westernization in the country. Turkey, this Middle Eastern nation, is a crossroads of cultures; therefore, three main layers of civilization influence the comportment of the Turkish persons cooperating in a larger team: their Turkic ethnic heritage, their Islamic religious heritage, and their commitment to European values. These three might seem contradictory at first sight, but they can be easily used to raise performance